Nutritional and physical activity knowledge association with body fat in adolescents - Ribeiro, José Carlos (2018)
Knowledge enhancement hás been referred as a mean to improve nutrition and physical activity, and reduce obesity. This work aimed to identify the difference ofnutrition and physical activity knowledge according to body fat and physical activity leveis in adolescents. Methods: This study vvas a cross sectional analysis involving 734 adolescents. Body fat was detennined using electric bioimpedance, and physical activity was assessed by accelerometer. Adolescents were divided in groups according to physical activity leveis (high versus low) aiid body fat (overfat veisus non-overfat). Thcy were then divided into four groups: "high physical activity/ non-overfat"; "high physical activity/ overfat"; "low physical activity/ non-overfat"; and "lowphysical activity/ overfat". Nutrition and Physical knowledge was assessed by questionnaires. Results: Body tat percentage exposed 30.8 % overfatí obcsc adolescents, and daily moderate to vigoroiis physical activity lasted in average 47.9 (SD=27. 49) minutes. High physical activity adolescents presented higher physical activity knowledge (p=. 044) and the low physical activity/overfat group scored fhe worst on experts' nutritional recommendations knowledge.